Determination Purchase Intention and Purchase Decision: Brand Image and Promotion Analysis (Marketing Management Literature Review) - Rahmadani Hidayat; Menhard Menhard; Chintya Ones Charli; Ariyanto Masnum; Budi Hartoyo (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This literature survey article discusses the impact of brand image and advertising on purchase intent and decision making with the aim of generating research hypotheses about the effects between variables that can be used in further research. The method of writing this literature review is a library research method derived from online media such as Google Scholar, Mendeley, and other online media. The results of this literature search are: 1) Brand image influences purchase intention. 2) Advertising influences purchase intent. 3) Brand image influences purchasing decisions. 4) Advertising influences purchasing decisions. 5) Purchase intent influences purchase decisions. It is hoped that future researchers will be able to add or study other variables that influence interest and purchase decisions, such as price, product quality, service quality, brand ambassadors, and trust.